Modified lithium titanium aluminum phosphate as well as preparation method and application thereof
By coating the surface of lithium titanium aluminum phosphate with a polyimide layer to form a modified lithium titanium aluminum phosphate with a composite structure, the problems of high moisture content, poor stability and insufficient electrolyte wettability of the lithium-ion battery separator are solved, the thermal stability and ionic conductivity of the battery are improved, and the safety and energy density of the battery are enhanced.
Patent Information
- Application Number
- CN202510857730.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2025-10-17
Smart Images

Figure BDA0005466524020000081
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of electrical devices, and particularly relates to a modified lithium aluminum titanium phosphate and a preparation method and application thereof. BACKGROUND
[0002] The lithium ion battery or capacitor separator is an important component in the lithium ion battery, and plays a role of isolating the positive and negative electrode sheets and conducting ions while isolating electrons. The conventional separator generally mainly adopts a polyolefin separator, but due to the lower thermal stability and liquid absorption and retention performance, the use thereof is limited. People often use a surface coating method to modify the separator to improve the thermal performance, ion conductivity and liquid absorption and retention performance of the separator, such as coating an inorganic material coating layer on the surface of a polyethylene separator to effectively improve the thermal performance of the separator and improve the liquid absorption and retention capacity of the separator. For example, alumina coating, but the large hardness and density thereof cause serious wear of the equipment during preparation, and the ion conductivity of the separator is not obviously improved. On this basis, people use solid electrolyte materials as the separator coating layer, such as lithium aluminum titanium phosphate (LATP) material, which has higher ion conductivity and better electrolyte wettability compared to alumina coating. However, Ti 4+ has poor electrochemical stability with lithium metal, and under low voltage conditions, Ti 4+ is easily reduced to Ti 3+ , and even forms a Li-Ti alloy, thereby causing the formation of a conductive phase, resulting in unstable batteries, and the water content of LATP is high, which causes the water content of the separator to be high, and it is difficult for conventional drying methods to make the separator meet the water content requirement of the battery, resulting in a decrease in the electrical performance of the separator. Therefore, it is still necessary to develop a separator with low water content, high stability, ion conductivity and electrolyte wettability. SUMMARY
[0003] In view of the problems of high water content and poor stability, ion conductivity and electrolyte wettability of the separator involved in the prior art, the present application provides a modified lithium aluminum titanium phosphate and a preparation method and application thereof.
[0004] To achieve the above-mentioned purpose, the following technical solutions are specifically included:
[0005] In a first aspect, the present application provides a preparation method of a modified lithium aluminum titanium phosphate, comprising the following steps:
[0006] (1) dissolving a monomer containing a binary amino group in an organic solvent, then adding a monomer containing a binary anhydride group, and performing a polymerization reaction to obtain a polyamide acid solution;
[0007] (2) adding lithium aluminum titanium phosphate into the polyamide acid solution, and performing stirring and mixing and granulation to obtain a composite particle;
[0008] (3) subjecting the composite particles to imidization treatment to obtain the modified lithium aluminum titanium phosphate.
[0009] The modified lithium aluminum titanium phosphate prepared by the above method is composed of a lithium aluminum titanium phosphate (LATP) core and a polyimide outer coating layer. The modified lithium aluminum titanium phosphate has the characteristics of low moisture content, small density, high temperature resistance, high wettability and high ionic conductivity, and can make the separator have the advantages of low area density and moisture content, and high thermal stability, ionic conductivity and electrolyte wettability.
[0010] Since the polyimide has a low density, the separator has a lower density, the area density of the separator is reduced, and the improvement of the battery energy density is facilitated. Due to the presence of the polyimide coating layer, the contact of LATP with electrolyte and electrode material and the contact of moisture are isolated, the occurrence of the electrochemical side reaction of LATP is slowed down, the stability of the separator is improved, the probability of adsorbing water is reduced, and the moisture content of the separator can be obviously reduced. At the same time, the polyimide in the outer coating layer is beneficial to improve the adhesion of the separator to the positive and negative electrode sheets, exclude the air in the internal gap of the adhesion part, enhance the hardness of the battery cell, reduce the thermal shrinkage of the separator, and further improve the thermal stability of the battery. In addition, due to the presence of aromatic ring and heterocyclic units in the molecular structure of polyimide, polyimide has high flame retardant performance, which can increase the high temperature stability of the separator, reduce the thermal shrinkage of the separator, and greatly enhance the safety performance of the battery. Therefore, the modified lithium aluminum titanium phosphate can further make the separator have the advantages of low area density and moisture content, and high thermal stability, ionic conductivity and electrolyte wettability on the basis of maintaining the good ionic conductivity and high liquid absorption performance of LATP.
[0011] In some embodiments, in step (1), the monomer containing a binary amino group includes at least one of 4,4'-diaminodiphenyl ether (ODA), 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), p-phenylenediamine or 4,4'-diaminodiphenylmethane.
[0012] In some embodiments, in step (1), the monomer containing a binary anhydride group includes at least one of pyromellitic dianhydride (PNDA), 3,3',4,4'-biphenyl tetracarboxylic dianhydride (BPDA), hexafluoroisopropyl phthalic anhydride (6FDA), 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) or hexafluoro dianhydride.
[0013] The use of the above two types of monomers makes the composite separator have lower area density and moisture content, higher thermal stability, ionic conductivity and electrolyte wettability.
[0014] In some embodiments, in step (1), the molar ratio of the binary amino-containing monomer and the binary anhydride group-containing monomer is (0.5-1.2):(0.5-1.2).
[0015] In some embodiments, in step (1), the organic solvent comprises at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), or N-methyl pyrrolidone (NMP).
[0016] In some embodiments, in step (1), the temperature of the polymerization reaction is -10℃ to 5℃.
[0017] In some embodiments, in step (1), the mass percentage of polyamic acid in the polyamic acid solution is 5%-30%. With the content of the polyamic acid solution in this range, the composite separator has lower areal density and moisture content, higher thermal stability, ion conductivity, and electrolyte wettability.
[0018] In some embodiments, in step (2), the average particle size of the lithium aluminum titanium phosphate is 50-5000 nm, and further preferably 300-500 nm. The average particle size of the lithium aluminum titanium phosphate is related to the density and water absorption performance of the coating on the separator. The inventors of the present application have found that selecting the average particle size of the lithium aluminum titanium phosphate to be 50-5000 nm is more conducive to the modification of the lithium aluminum titanium phosphate, and thus the modified lithium aluminum titanium phosphate has the characteristics of low moisture content, small density, high temperature resistance, high wettability, and high ion conductivity, further enabling the separator to have the advantages of low areal density and moisture content, high thermal stability, high ion conductivity, and high electrolyte wettability.
[0019] In some embodiments, in step (2), the mass ratio of the lithium aluminum titanium phosphate to the polyamic acid solution is 1:(0.1-0.3).
[0020] In some embodiments, in step (2), the granulation method comprises at least one of electrostatic spraying or spray drying.
[0021] In some embodiments, the temperature of the spray drying is 30-80℃, and the time of the spray drying is 1-10h.
[0022] In some embodiments, in step (3), the temperature of the imidization treatment is 300-350℃, and the time of the imidization treatment is 1-3h.
[0023] In a second aspect, the present application provides a modified lithium aluminum titanium phosphate, which is prepared by the method for preparing the modified lithium aluminum titanium phosphate. The modified lithium aluminum titanium phosphate comprises lithium aluminum titanium phosphate and a coating layer covering the lithium aluminum titanium phosphate, and the coating layer comprises polyimide.
[0024] In some embodiments, the coating layer has a thickness of 3-200 nm.
[0025] In some embodiments, the base film has a thickness of 3-20 μm.
[0026] In some embodiments, the base film comprises at least one of a polyolefin film, a cellulose film, or a polyester film.
[0027] In some embodiments, the polyolefin film comprises at least one of a polyethylene (PE) film or a polypropylene (PP) film.
[0028] In some embodiments, the base film has a thickness of 3-20 μm.
[0029] In some embodiments, the coating layer has a thickness of 1-5 μm. With the coating layer thickness in this range, the composite separator has a lower areal density and moisture content, and higher thermal stability, ionic conductivity, and electrolyte wettability.
[0030] In some embodiments, the coating layer further comprises at least one of a dispersant, a thickening agent, a binder, or a wetting agent.
[0031] In some embodiments, the dispersant comprises at least one of ammonium polyacrylate, sodium polyacrylate, polyacrylamide, polycarboxylate, polyvinyl alcohol, silicate colloid, or propylene glycol block polyether; and the mass percentage of the dispersant based on the mass of the coating layer is 0.1%-1%.
[0032] In some embodiments, the thickening agent comprises at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, hydroxyethyl cellulose, polyvinyl alcohol-polyacrylic acid copolymer, polyvinylpyrrolidone; and the mass percentage of the thickening agent based on the mass of the coating layer is 0.5%-2%.
[0033] In some embodiments, the binder comprises one or more of styrene-butadiene latex, vinyl acetate latex, polybutyl methacrylate, polyacrylic acid ester, polymethyl methacrylate, polyvinylidene fluoride, etc.; and the mass percentage of the binder based on the mass of the coating layer is 1%-10%.
[0034] In some embodiments, the wetting agent comprises at least one of sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium butylnaphthalene sulfonate, sodium isopropyl naphthalene sulfonate; and the mass percentage of the wetting agent based on the mass of the coating layer is 0.1%-2%.
[0035] In some embodiments, the mass percentage of the modified titanium aluminum lithium phosphate is 85%-95% based on the mass of the coating.
[0036] The coating can be disposed on the base film in a conventional manner, for example, can include the following manner: uniformly mixing raw materials of the coating with a solvent to obtain a coating slurry; then coating the coating slurry on the base film, and drying to obtain the composite separator.
[0037] In some embodiments, the solvent includes at least one of deionized water, anhydrous ethanol, NMP, and DMF.
[0038] In a fourth aspect, the present application provides an electronic device comprising the composite separator.
[0039] In some embodiments, the electronic device includes at least one of a lithium ion battery or a capacitor.
[0040] In some embodiments, the lithium ion battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator disposed between the positive electrode sheet and the negative electrode sheet, and the separator includes the composite separator.
[0041] In some embodiments, the positive electrode sheet includes a positive electrode active material.
[0042] In some embodiments, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of lithium cobaltate, lithium nickel cobaltate, lithium manganate, lithium nickel manganate, ternary lithium nickel cobalt manganate, lithium nickel cobalt aluminumate, lithium nickel cobalt manganese aluminumate, lithium manganese iron phosphate, lithium iron phosphate, sulfur, or lithium sulfide.
[0043] In some embodiments, the mass percentage of the positive electrode active material is 60%-99% based on the total mass of the positive electrode sheet.
[0044] In some embodiments, the positive electrode sheet further includes a binder and a conductive agent.
[0045] In some embodiments, the binder includes at least one of styrene butadiene rubber, water-based acrylic resin, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, ethylene-vinyl acetate copolymer, or polyvinyl alcohol, and is not limited to the above-mentioned types, and the binder can be selected according to actual needs.
[0046] In some embodiments, the mass percentage of the binder is less than or equal to 5% based on the total mass of the positive electrode sheet.
[0047] In some embodiments, the conductive agent includes at least one of graphite, acetylene black, carbon black, ketjen black, carbon nanotube, graphene, or carbon nanofiber, but is not limited to the above, and the conductive agent can be selected according to actual needs.
[0048] In some embodiments, the mass percentage of the conductive agent is 1% to 3% based on the total mass of the positive electrode tab.
[0049] The positive electrode tab can be prepared by a conventional preparation method in the art. For example, the preparation method of the positive electrode tab includes the following steps: mixing a solvent, a conductive agent, a binder, and a positive electrode active material to obtain a positive electrode slurry; coating the positive electrode slurry on one side surface of a current collector, and performing drying and cold pressing to obtain the positive electrode tab.
[0050] In some embodiments, the current collector includes at least one of a copper foil or an aluminum foil.
[0051] In some embodiments, the solvent can include N-methyl pyrrolidone, but is not limited thereto.
[0052] In some embodiments, the negative electrode tab includes a negative electrode active material.
[0053] In some embodiments, the negative electrode active material includes at least one of lithium metal, a lithium metal alloy, graphite, silicon, silicon-oxygen, silicon-carbon, or silicon-oxygen-carbon, but is not limited thereto.
[0054] In some embodiments, the mass percentage of the negative electrode active material is 60%-99% based on the total mass of the negative electrode tab.
[0055] In some embodiments, the negative electrode tab further includes a binder and a conductive agent.
[0056] The negative electrode tab can be prepared by a conventional preparation method in the art. For example, the preparation method of the negative electrode tab includes the following steps: mixing a solvent, a conductive agent, a binder, and a negative electrode active material to obtain a negative electrode slurry; coating the negative electrode slurry on one side surface of a current collector, and performing drying and cold pressing to obtain the negative electrode tab.
[0057] Compared with the prior art, the modified lithium aluminum titanium phosphate of the present application has the following advantages: the modified lithium aluminum titanium phosphate is composed of a lithium aluminum titanium phosphate (LATP) core and a polyimide outer coating layer, and has the characteristics of low moisture content, small density, high temperature resistance, high wettability, and high ionic conductivity, so that the separator has the advantages of low areal density and moisture content, high thermal stability, high ionic conductivity, and high electrolyte wettability. In addition, the preparation process of the modified lithium aluminum titanium phosphate of the present application is simple, the cost is low, and it is suitable for actual large-scale production. DETAILED DESCRIPTION
[0058] To better illustrate the objectives, technical solutions, and advantages of the present invention, the present invention will be further described below with reference to specific examples. The experimental methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials and reagents used are commercially available unless otherwise specified.
[0059] Example 1
[0060] A method for preparing a composite diaphragm comprises the following steps:
[0061] S1. Weigh pyromellitic dianhydride and p-phenylenediamine in a molar ratio of 1:1, dissolve the p-phenylenediamine in N,N-dimethylformamide (DMF) solvent, and stir thoroughly until completely dissolved. Add pyromellitic dianhydride in an ice-water bath, and continue stirring to allow the mixed solution to react fully to obtain a polyamic acid solution, wherein the polyamic acid solution contains 10 wt % of polyamic acid and 90 wt % of DMF;
[0062] S2. Then, LATP powder with a particle size of D50 = 500 nm was added to the polyamic acid solution, with the mass ratio of LATP powder to the polyamic acid solution being 1:0.2, and stirring was continued to mix them evenly to obtain a mixed solution; the mixed solution was spray-dried to obtain polyamic acid / LATP composite particles, and then dried in a forced air drying oven at 70° C.;
[0063] S3, imidizing the composite particles in a thermal reaction furnace at a temperature of 300° C., a heating rate of 2° C. / min, and a holding time of 2 h to obtain modified lithium aluminum titanium phosphate, which is a composite microsphere of polyimide-coated LATP;
[0064] S4. Based on the coating mass, 0.5wt% ammonium polyacrylate, 1wt% sodium carboxymethyl cellulose, 5wt% styrene-butadiene latex, 0.5% sodium lauryl sulfate and 93wt% modified lithium aluminum titanium phosphate are mixed with water to prepare a slurry, and then the mixed slurry is coated on one surface of a polyethylene base film with a thickness of 9μm on one side. After drying at 50°C, a coating is formed on the base film to obtain a composite diaphragm with a coating thickness of 3μm.
[0065] Example 2
[0066] The difference between this embodiment and embodiment 1 is that in step S1, pyromellitic dianhydride and p-phenylenediamine are weighed in a molar ratio of 1:1, and their masses are increased so that the mass percentage of polyamic acid in the prepared polyamic acid solution is 20%, and the rest are the same.
[0067] Example 3
[0068] The difference between the present example and Example 1 is that in step S1, pyromellitic dianhydride and p-phenylenediamine are weighed according to a molar ratio of 1:1, and the mass of both is increased, so that the mass percentage of polyamic acid in the prepared polyamic acid solution is 30%, and the rest is the same.
[0069] Example 4
[0070] The difference between the present example and Example 1 is that in step S2, the LATP powder with D50 = 300 nm is used, and the rest is the same.
[0071] Comparative Example 1
[0072] The difference between the present comparative example and Example 1 is that the present comparative example does not perform the modification process of steps S1-S3, and directly uses the LATP powder with D50 = 500 nm to replace the modified lithium aluminum titanium phosphate to prepare the composite separator, and the rest is the same.
[0073] Comparative Example 2
[0074] The difference between the present comparative example and Comparative Example 1 is that the LATP powder with particle size of D50 = 300 nm is used to replace the LATP powder with D50 = 500 nm, and the rest is the same.
[0075] Comparative Example 3
[0076] The difference between the present comparative example and Example 1 is that the present comparative example does not prepare a coating on the surface of the 9 μm thick polyvinyl film, and directly uses the original 9 μm thick polyvinyl film as the separator.
[0077] The separators obtained in the above examples and comparative examples are tested for areal density, thermal stability, ion conductivity and moisture value, wherein the thermal stability test is to transfer the separator at room temperature (25℃) to heat treatment at 150℃ for 1h, and test the longitudinal (MD) and transverse (TD) direction size shrinkage rate (%) of the separator before and after heat treatment, when the thermal shrinkage rate is <3%, the thermal shrinkage performance of the separator is qualified, and when the thermal shrinkage rate is >5%, it cannot be applied; the moisture value is tested by Karl Fischer method; the test results are shown in Table 1.
[0078] Table 1
[0079]
[0080] The areal density of the composite separator of the present application is 8.50-8.85 g / cm 2 , the thermal shrinkage performance (MD and TD directions) at 150℃ for 1h is less than 3%, the ion conductivity is as high as (7.8-8.2) x 10 -4 S / cm, and the moisture value is as low as 1000 ppm.
[0081] It can be seen from Comparative Example 1-2 and Comparative Example 3 that coating the coating layer containing LATP on the base film reduces the heat shrinkage of the separator to some extent, improves the thermal stability of the separator, and also improves the ionic conductivity of the separator, because the presence of the coating layer improves the liquid absorption and retention of the separator. However, the coating layer significantly increases the areal density and moisture value of the composite separator. Compared with Comparative Example 1-2 and Example 1, the modified titanium aluminum lithium phosphate obtained by modifying LATP with a polyimide coating in the present application can significantly reduce the areal density and moisture of the separator while maintaining a high ionic conductivity; the reduction in areal density is conducive to improving the energy density of the battery; because LATP further removes moisture during polyamide acid imidization, and the presence of the polyimide coating layer prevents the contact of LATP with moisture in the air and reduces the contact of the slurry with water during slurry preparation, further reducing the probability of adsorbing moisture, the coating of polyimide can significantly reduce the moisture value of the composite separator, and the low moisture content of the composite separator is conducive to improving the subsequent electrical performance of the separator.
[0082] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present application and are not intended to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present application.
Claims
1. A method for preparing modified lithium aluminum titanium phosphate, characterized in that: The steps include: (1) dissolving a monomer containing a dibasic amino group in an organic solvent, and then adding a monomer containing a dibasic acid anhydride group to carry out a polymerization reaction to obtain a polyamic acid solution; (2) adding lithium aluminum titanium phosphate to the polyamic acid solution, stirring and mixing, and granulating to obtain composite particles; (3) The composite particles are subjected to imidization treatment to obtain the modified lithium aluminum titanium phosphate.
2. The method for preparing modified lithium aluminum titanium phosphate according to claim 1, wherein: In step (1), the diamino group-containing monomer includes at least one of 4,4'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)diaminobiphenyl, p-phenylenediamine or 4,4'-diaminodiphenylmethane.
3. The method for preparing modified lithium aluminum titanium phosphate according to claim 1, wherein: In step (1), the monomer containing a dibasic acid anhydride group includes at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, hexafluoroisopropylphthalic anhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride or hexafluorodianhydride.
4. The method for preparing modified lithium aluminum titanium phosphate according to claim 1, wherein: Include at least one of the following AC: A. In step (1), the polymerization reaction temperature is -10°C to 5°C; B. In step (1), the mass percentage of polyamic acid in the polyamic acid solution is 5%-30%; C. In step (1), the molar ratio of the monomer containing a diamino group to the monomer containing a dibasic acid anhydride group is (0.5-1.2): (0.5-1.2).
5. The method for preparing modified lithium aluminum titanium phosphate according to claim 1, wherein: Include at least one of the following DE: D. In step (2), the mass ratio of the lithium aluminum titanium phosphate to the polyamic acid solution is 1:(0.1-0.3); E. In step (2), the granulation method includes at least one of electrostatic spraying or spray drying.
6. The method for preparing modified lithium aluminum titanium phosphate according to claim 1, wherein: In step (3), the temperature of the imidization treatment is 300-350° C., and the time of the imidization treatment is 1-3 hours.
7. The method for preparing modified lithium aluminum titanium phosphate according to claim 1, wherein: In step (2), the average particle size of the lithium aluminum titanium phosphate is 50-5000 nm.
8. A modified lithium aluminum titanium phosphate, characterized in that: The modified lithium titanium aluminum phosphate is prepared by the preparation method of any one of claims 1 to 7, wherein the modified lithium titanium aluminum phosphate comprises lithium titanium aluminum phosphate and a coating layer coating the lithium titanium aluminum phosphate, and the coating layer comprises polyimide.
9. A composite diaphragm, characterized in that: It comprises a base film and a coating arranged on the surface of the base film, wherein the coating comprises the modified lithium aluminum titanium phosphate according to claim 8.
10. An electronic device, characterized in that: Including the composite diaphragm according to claim 9.